A Switched Capacitor Based DC-DC Converter with Common Grounding for Fuel Cell Vehicle - Kumar A.; Wang Y.; Xiong X.; Pan X.; Kumar Singh S. (My University, 2025)
To suffice the requirement of FCV, a DC-DC converter must have continuous high voltage gain, continuous input current, common grounding between input and output, low electromagnetic interference issues. Besides these, DC-DC converter should be compact with lower voltage stress across different components. A new DCDC converter is proposed which is structured by combining quasi switched boost network and switched capacitor network in this paper to fulfill above requirements. The proposed converter steady state analysis, stress analysis, comparative analysis is presented in this paper. A 200 W power rating converter is validated in experiment. © 2020 IEEE.